The evaluation of some hematological parameters of human tuberculosis in Thi-Qar Province - Manal Al-Tamemi (مجلة علوم ذي قار, 2019)
The present study aimed to evaluation of erythrocyte sedimentation rate (ESR), hemoglobin (Hb.) levels, white blood cell count (WBCs) in active and latent tuberculosis patients in Thi-Qar province,Iraq. This study included 210 samples (70 patients, 70 household contacts and 70 control ) with age's ≤10 to ≥70 years who were referred to ALNasiriya Center of Tuberculosis and Chest Diseases from the period September 2012—July 2013.The study showed that